Observer Variability in Evaluating Pisotriquetral Osteoarthritis using Pisotriquetral View - Heeg, Erik; ten Berg, Paul W. L.; Maas, Mario; Strackee, Simon D. (Journal of Hand and Microsurgery, 2017)
A pisotriquetral (semilateral) view of the wrist may improve the assessment of pisotriquetral osteoarthritis (OA), but its reliability and reproducibility are unclear. The purpose of this cross-sectional observer study was to investigate (1) the inter- and intraobserver agreement of evaluating pisotriquetral OA using pisotriquetral views with a special focus on sclerosis, joint space width (JSW) narrowing and osteophyte formation, and (2) the incidence of these latter radiographic features in patients suspected for pisotriquetral OA. Five independent observers rated independently at two different occasions 27 pisotriquetral views from patients treated for ulnar-sided wrist pain suspected for pisotriquetral OA requiring a pisiform resection. The agreement was calculated using kappa statistic. Agreement between observers ranged from 0.38 (fair) to 0.56 (moderate). Average intraobserver agreement ranged from 0.43 (moderate) to 0.52 (moderate). In 36% of the ratings, JSW narrowing was observed, followed by osteophyte formation (30%) and sclerosis (28%). Observers found it especially difficult to detect JSW narrowing. Despite the availability of a pisotriquetral view to enhance visualization of the pisotriquetral joint, assessment of the specific features indicating pisotriquetral OA leads to only fair-to-moderate agreement. This limits the applicability of a radiographic assessment. A rationale for a more reliable radiologic approach in assessing the level of pisotriquetral OA is needed, which may require the use of more advanced imaging techniques.
Keywords: pisiform; triquetral; pisotriquetral joint; pisotriquetral osteoarthritis; observer